FAKTOR FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP MASYARAKAT KARUBAGA DISTRICT SUB DISTRICT TOLIKARA PROPINSI PAPUA - Delwien Esther Jacob; Sandjaya Sandjaya (Jurnal Nasional Ilmu Kesehatan, 2018)
Background : Quality life are individual perception about his position in the life based on culture, system of value which related with purpose of life, hope, standart and all related ones. Problems that related with quality of life are phisical health status, phsicology status, personal social and environment.Objectives : The objective of this research are to know the factors that affecting society of Karubaga District, Tolikara region quality of life.Method : This research are cross sectional research, in Health Department of Tolikara region. Population are all society of Karubaga District which in age range between 18 to 40 years old. The data was came from quisioner and be analyzed with chi-square test. Result: Quality of life from society of Karubaga District were affecting by physical factors (p-value0,000;RP= 4,030; CI95% = 2,120 – 7,664), phsicology factors (p-value0,000; RP= 4,788; CI95% = 2,560 – 8,955), social factors (p-value0,000; RP= 7,875; CI95%= 4,342 – 14,282) and environment factors (p-value0,000; RP= 23,324; CI95%= 5,591 – 89,125).Dominan factors that affecting quality of life society of Karubaga district was environment factors. Key Words : Physical, Phsicology, Social, Environment, Quality of Life.